Beliefs and Practices of EFL Instructors in Teaching Pronunciation - Sakineh Jafari; Mohammad Reza Karimi; Samaneh Jafari (Vision: Journal for Language and Foreign Language Learning, 2021)
Pronunciation teaching and learning have stimulated a renewed interest among second language acquisition (SLA) researchers in the past few years. To pursue this line of inquiry, this study set out to investigate the beliefs and practices of Iranian EFL teachers on pronunciation teaching. Convenience sampling was employed to recruit 74 participants who completed a pronunciation teaching and learning questionnaire. Interviews were also conducted with volunteered participants. The results revealed that 57% of the respondent teachers mostly worked on suffixes such as the -ed and -s endings always or often in their classrooms. The second most frequently taught feature was word stress (54%), followed by syllable structure, which 53% of the teachers often or always taught. Drama and role-play were the most common strategies often or always used by 49% of the teachers in teaching pronunciation. In addition, interviews with participant teachers revealed that the most common classroom activities were imitation and repetition. Finally, although most participants emphasized the need to teach pronunciation, they did not consider themselves highly qualified. They indicated an insatiable desire for more pronunciation training in teacher education programs to use opportunistic teaching and integrated phases to teach pronunciation. Most of the teachers did not teach pronunciation as a separate lesson since the school curriculum, the pre-specified book, and the time limitation did not let them focus on pronunciation as a separate lesson.